Phenotypic analysis of Longya-10 × pale flax hybrid progeny and identification of candidate genes regulating prostrate/erect growth in flax plants - Qi, Yanni; Wang, Limin; Li, Wenjuan; Xie, Yaping; Zhao, Wei; Dang, Zhao; Li, Wen; Zhao, Lirong; Zhang, Jianping (Frontiers in Plant Science, 2022)
Flax is a dual-purpose crop that is important for oil and fiber production. The growth habit is one of the crucial targets of selection during flax domestication. Wild hybridization between cultivated flax and wild flax can produce superior germplasms for flax breeding and facilitate the study of the genetic mechanism underlying agronomically important traits. In this study, we used pale flax, Linum grandiflorum, and L. perenne to pollinate Longya-10. Only pale flax interspecific hybrids were obtained, and the trait analysis of the F1 and F2 generations showed that the traits analyzed in this study exhibited disparate genetic characteristics. In the F1 generation, only one trait, i.e., the number of capsules per plant (140) showed significant heterosis, while the characteristics of other traits were closely associated with those of the parents or a decline in hybrid phenotypes. The traits of the F2 generation were widely separated, and the variation coefficient ranged from 9.96% to 146.15%. The quantitative trait locus underlying growth habit was preliminarily found to be situated on chromosome 2 through Bulked-segregant analysis sequencing. Then linkage mapping analysis was performed to fine-map GH2.1 to a 23.5-kb interval containing 4 genes. Among them, L.us.o.m.scaffold22.109 and L.us.o.m.scaffold22.112 contained nonsynonymous SNPs with ∆index=1. Combined with the qRT-PCR results, the two genes might be possible candidate genes for GH2.1. This study will contribute to the development of important germplasms for flax breeding, which would facilitate the elucidation of the genetic mechanisms regulating the growth habit and development of an ideal architecture for the flax plant.